Development of low‐melting‐point filler materials for laser beam brazing of aluminum alloys. Issue 8 (26th August 2014) - Cui, C.; Schulz, A.; Achelis, L.; Uhlenwinkel, V.; Leopold, H.; Piwek, V.; Tang, Z.; Seefeld, T.
<x xml:space="preserve">Abstract</x> In order to develop low‐melting‐point filler materials for laser beam brazing of aluminum alloys, Al–Si–Cu based alloys and Al–Si–Zn based alloys were produced via spray forming and associated deformation processes. The selected alloys were spray formed in the form of billet with a diameter around 160 mm and hot extruded into wire rods with a diameter of 8 mm. The extrusions were further cold worked into thin wires with a diameter of 1.2 mm via rotary swaging. Finally, the filler wires were applied in the laser beam brazing of AA6082 structures. It showed that the newly developed filler materials could meet the requirements of the laser beam brazing of aluminum alloys. Particularly, the laser beam brazing process using the spray‐formed filler materials required a significantly lower energy input and allowed for higher brazing speed as compared to the conventional AlSi12 filler material.